Peculiarities of platelet hemostasis changes in COPD - hypertensive disease mixed patients - Svitlana O. Samoilova; Olga M. Plenova (Kazimierz Wielki University, 2016)
Samoilova Svitlana O., Plenova Olga M. Peculiarities of platelet hemostasis changes in COPD - hypertensive disease mixed patients. Journal of Education, Health and Sport. 2016;6(4):39-44. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.49394 http://ojs.ukw.edu.pl/index.php/johs/article/view/3445   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.03.2016. Revised 20.03.2016. Accepted: 05.04.2016.     Peculiarities of platelet hemostasis changes in COPD - hypertensive disease mixed patients   Svitlana O. Samoilova, Olga M. Plenova   O.O.Bohomolets National Medical University   Abstract   Disorders in the hemostasis system have a major impact on the disease course and complication in the hypertensive disease and chronic obstructive pulmonary disease patients. To assess the platelet hemostasis we examined 62 persons: 15 apparently healthy (Control Group), 15 HD patients without COPD, 17 HD patients with COPD associated, and 15 COPD patients of Degree II and III. We have found out that HD, COPD and the mix patients demonstrate an increased thrombocyte functional activity expressed in a higher degree of spontaneous aggregation, and significant activation of arachidonic acid induced thrombocyte aggregation. The HD patients feature a specific increase of adrenalin induced aggregation, contrary to other examined groups, that may be explained by a role of sympathetic nervous system in the HD pathogenesis. Chronic inflammation in the COPD patients is accompanied with a significant increase of arachidonic acid thrombocyte reaction (the highest among all examined groups) that should be taken into account when establishing a treatment policy with anti-inflammatory agents included.   Key words: hypertensive disease, chronic obstructive pulmonary diseases, hemostasis, thrombocytes, aggregation.